Typing of Mycoplasma pneumoniae by PCR-mediated DNA fingerprinting. - Ursi, D (1994)
PCR fingerprinting was used to characterize clinical isolates of Mycoplasma pneumoniae. Among 24 strains tested, two types were distinguished. Nineteen strains belonged to type 1, whereas only 5 strains belonged to type 2. The majority of strains isolated since 1991 in Belgium belong to type 1. No variations in fingerprinting patterns were observed within each group, confirming the highly conserved nature of the M. pneumoniae genome.